2021
DOI: 10.1111/geb.13411
|View full text |Cite
|
Sign up to set email alerts
|

Vascular epiphytes contribute disproportionately to global centres of plant diversity

Abstract: This is an open access article under the terms of the Creat ive Commo ns Attri bution License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
66
0
5

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 66 publications
(73 citation statements)
references
References 81 publications
2
66
0
5
Order By: Relevance
“…In general, the systematic composition of Amazonian epiphyte communities is highly predictable at the family level with Orchidaceae, Araceae and Bromeliaceae being the most speciesrich families (Kreft et al, 2004). This pattern was reported earlier by Taylor et al (2021), using inventories and distribution information for 27,850 epiphyte species derived from literature sources, where Orchidaceae comprises 67% of the epiphytic flora, Bromeliaceae (11%) and Araceae (4%) being the dominant plant families. Marcusso et al (2022) it also reported this same pattern for the Neotropics and our results confirm this for Amazonia.…”
Section: Discussionsupporting
confidence: 57%
See 2 more Smart Citations
“…In general, the systematic composition of Amazonian epiphyte communities is highly predictable at the family level with Orchidaceae, Araceae and Bromeliaceae being the most speciesrich families (Kreft et al, 2004). This pattern was reported earlier by Taylor et al (2021), using inventories and distribution information for 27,850 epiphyte species derived from literature sources, where Orchidaceae comprises 67% of the epiphytic flora, Bromeliaceae (11%) and Araceae (4%) being the dominant plant families. Marcusso et al (2022) it also reported this same pattern for the Neotropics and our results confirm this for Amazonia.…”
Section: Discussionsupporting
confidence: 57%
“…Even in relatively close areas, where soil gradients cause changes in tree composition, marked differences are found in the composition of vascular epiphytes (Boelter et al, 2014;Quaresma et al, 2017). On the other hand, recent studies with vascular epiphytes on a global scale strongly suggest that epiphytes vary relative to trees in their responses to environmental gradients, with epiphytes responding more quickly to the atmospheric gradient due to their air and water-limited growth habit (Taylor et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This result agrees with the importance of biotic interactions as prerequisites for biodiversity accumulation, which has been postulated on geological timescales ( 70 ). Specifically, it seems likely that high precipitation (in warm areas) allows tropical rainforest to occur, which in turn, allows a variety of growth forms to coexist [including an astonishing diversity of epiphytes ( 36 )]. This is not possible where rainforest cannot occur despite the right climate (e.g., for edaphic reasons [edaphic savannas, wetlands]).…”
Section: Discussionmentioning
confidence: 99%
“…Vegetation greatly modifies the environment by influencing local climatic and edaphic conditions and creating microhabitats, allowing for niche differentiation. For example, trees create a dynamic mosaic of light and shade ( 35 ) and form a complex substrate for epiphytes, which have recently been shown to contribute substantially to global plant diversity patterns ( 36 ). Although the distribution of biomes often mirrors the abiotic environment, such as climate and soils, this is not always the case ( 37 ).…”
mentioning
confidence: 99%